2020
DOI: 10.1016/j.toxicon.2020.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cross-reactive human single-chain variable fragments against phospholipases A2 from Lachesis muta and Bothrops spp venoms

Abstract: Identification of cross-reactive human single-chain variable fragments against phospholipases A 2 from Lachesis muta and Bothrops spp venoms, Toxicon (2020), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Campos et al. demonstrated that when snake whole venoms were used as targets in phage display panning rounds, antibodies were primarily selected against PLA 2 proteins ( 180 ). To overcome this difficulty, key toxins that are important to neutralize, but which are not dominant in neither phage display campaigns or immunization schemes, can be carefully isolated or recombinantly expressed to provide more control over the antibody selection or immunization process ( 188 190 ).…”
Section: Therapeutics Against C D Ruruima Envenomingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Campos et al. demonstrated that when snake whole venoms were used as targets in phage display panning rounds, antibodies were primarily selected against PLA 2 proteins ( 180 ). To overcome this difficulty, key toxins that are important to neutralize, but which are not dominant in neither phage display campaigns or immunization schemes, can be carefully isolated or recombinantly expressed to provide more control over the antibody selection or immunization process ( 188 190 ).…”
Section: Therapeutics Against C D Ruruima Envenomingsmentioning
confidence: 99%
“…However, further into the future, it is not unlikely that recombinant DNA technology and the application of human monoclonal antibodies and/or nanobodies may find their way into the field (176). Indeed, the development of monoclonal antibodies to treat envenomings caused by venomous animals is now being extensively investigated (177)(178)(179)(180)(181), although none have so far been tested in human patients. Here, we will explore only the discoveries regarding experimental crotalid antivenoms.…”
Section: Heterologous Antivenom Disadvantages and Next-generation Crotalid Antivenomsmentioning
confidence: 99%
“…Part of the explanation for this may be that PLA 2 s seem to dominate as antigens compared to other venom components. Campos et al demonstrated that when snake whole venoms were used as targets in phage display panning rounds, antibodies were primarily selected against PLA 2 proteins [180]. To overcome this difficulty, key toxins that are important to neutralize, but which are not dominant in neither phage display campaigns or immunization schemes, can be carefully isolated or recombinantly expressed to provide more control over the antibody selection or immunization process [188][189][190].…”
Section: Heterologous Antivenom Disadvantages and Next-generation Crotalid Antivenomsmentioning
confidence: 99%
“…The specific official treatment for snakebite envenoming is performed through an intravenous administration of monovalent or polyvalent antivenom, of which the manufacturing procedure has remained practically the same over a hundred years, with no significant changes. However, other procedures have been investigated to improve antivenom therapy, based on antibody technologies (Knudsen et al, 2019;Campos et al, 2020). Antivenom is effective in preventing death of victims, but, by contrast, it has some drawbacks: low capability to inhibit local effects of venoms, low stability in liquid form, thermolability, high cost of production, and in some cases, antivenom may produce fever or anaphylactic reactions (Williams et al, 2019b;Gómez-Betancur et al, 2019).…”
mentioning
confidence: 99%
“…Antivenom is effective in preventing death of victims, but, by contrast, it has some drawbacks: low capability to inhibit local effects of venoms, low stability in liquid form, thermolability, high cost of production, and in some cases, antivenom may produce fever or anaphylactic reactions (Williams et al, 2019b;Gómez-Betancur et al, 2019). Thus, the limited efficacy of antivenoms may justify alternative therapies, which include monoclonal antibodies, aptamers, molecules derived from sponges, seaweed, plants or organic synthesis (Williams et al, 2019b;Campos et al, 2020;Ascoët, Ward, 2020;Faioli et al, 2013;da Silva et al, 2017;de Oliveira et al, 2016;Domingos et al, 2013;Pucca et al, 2019). Triazole is a five-membered heterocyclic compound containing three nitrogen atoms, with two isomeric forms (1,2,3-triazole or 1,2,4-triazole).…”
mentioning
confidence: 99%